2013
DOI: 10.4161/cbt.26341
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy agents-induced immunoresistance in lung cancer cells could be reversed by trop-2 inhibition in vitro and in vivo by interaction with MAPK signaling pathway

Abstract: Chemotherapy has been widely used in cancer treatment, but the prognosis of the cancer patients following chemotherapy has not been substantially improved. Alternative strategies such as immunotherapy and their combinations with chemotherapy are now being considered; however, the effects of chemotherapy on the immune responses of cancer cells are not fully understood. In the present studies, we reveal a potential link between chemotherapy and cancer immunoresistance, we first examined the effects of chemopreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Additionally, Trop-2 is a strong predictor of cancer response to AKT inhibitors, and as such AKT inhibitors seem to be a rational target for further investigation along with Trop-2-targeted therapy 70. Moreover, Wang et al have demonstrated that increased Trop-2 expression is associated with cisplatin resistance in lung cancer cells 71. Given the benefit of IMMU-132 (sacituzumab govitecan) therapy, which provides additional benefit at lower dosages than using irinotecan, this study demonstrates additional potential benefits of combining Trop-2-targeted therapeutics and traditional DNA-damaging chemotherapy, as we theorize Trop-2 inhibition may sensitize cells to DNA-damaging chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Trop-2 is a strong predictor of cancer response to AKT inhibitors, and as such AKT inhibitors seem to be a rational target for further investigation along with Trop-2-targeted therapy 70. Moreover, Wang et al have demonstrated that increased Trop-2 expression is associated with cisplatin resistance in lung cancer cells 71. Given the benefit of IMMU-132 (sacituzumab govitecan) therapy, which provides additional benefit at lower dosages than using irinotecan, this study demonstrates additional potential benefits of combining Trop-2-targeted therapeutics and traditional DNA-damaging chemotherapy, as we theorize Trop-2 inhibition may sensitize cells to DNA-damaging chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer xenografts, Trop2 was upregulated in relapsed tumors after flutamide and docetaxel treatment and Trop2 enhanced recovery of androgen-sensitive, but not androgen-resistant cells, after exposure to docetaxel [ 145 ]. Silencing Trop2 using shRNA resulted in increased sensitivity to cisplatin in lung and cisplatin/5-fluorouracil in gastric cancer cells in vitro and in vivo [ 146 , 147 ].…”
Section: Trop2 In Cancermentioning
confidence: 99%
“…The drug-surviving cells (DSCs) are responsible for tumor regeneration after chemotherapy, and may be one of the mechanisms involved in drug resistance ( 3 ). Immunoresistance induced by chemotherapy agents may be another mechanism ( 4 ). Am1010, a new DSC line, was established in our previous study from an arm muscle metastasic tumor of a patient diagnosed with lung adenocarcinoma ( 5 ).…”
Section: Introductionmentioning
confidence: 99%